Depicting the Prototype Change in Rural Consumer Behaviour: An Empirical Survey on Online Purchase Intention. Issue 2 (December 2021) - Ghosal, Indrajit; Prasad, Bikram; Behera, Mukti Prakash; Kumar, Atul
E-commerce is an undeniable growth opportunity. The infrastructure of e-commerce has been successful in making their system resilience in this age of VUCA (volatility, uncertainty, complexity and ambiguity). Besides during the time of pandemic, e-commerce have accomplished in meeting the demand of the consumers crossing various obstacles and scarcity of resource across the colours of socio-economic stratification of India. A detailed investigation of social, cultural, behavioural norms along with effect of socio-cultural regions has been investigated to strengthen the research. The method of cluster analysis has been used to segment the consumers into homogeneous subsets. The implied findings of this research will help the digital entrepreneurs to know their target consumers. Through cluster analysis, six clusters have been identified and they are named as, (a) Advanced changers; (b) Price sensitive; (c) Enthusiasts; (d) Realistic and logical; (e) Conservatives; (f) Unconcerned. The outcomes of this research can help the strategy managers and intrapreneurs to make informed decisions. This study can be of value addition for startups, digital entrepreneurs to start their own business through online shopping portals. The extracted results can help the marketing managers to know about the specific attributes of the consumers of rural areas which will lead to framing strategy according to market design, market space and marketplace.